Molecular Dynamics Investigation of Liquid and Vapor Interactions Near an Evaporating Interface: A Theoretical Genetics Perspective. Issue 7 (19th May 2020) - Montazeri, Kimia; Hao, Shuai; Abdolhosseini Qomi, Mohammad Javad; Won, Yoonjin
Abstract: Understanding phase transition between the liquid and gaseous states has gained significant interest, and has been ubiquitously observed in many places ranging from natural systems to water–energy nexus and thermal management applications. Phase transition phenomena at liquid–vapor interfaces are greatly governed by intermolecular‐level kinetics, which requires the use of empirical parameters in continuum‐level relations to explain the discrete nature of molecular particles. Despite its significance, it has been a great challenge to find detailed expressions of empirical parameters such as accommodation coefficients, which represent the probabilities for phase transition of liquid or vapor molecules at the interface. Here, direct statistical measurements of accommodation coefficients are reported by tracking the trajectories of liquid and vapor molecules in molecular simulations. The measurements reveal that evaporation and condensation coefficients are different by ≈50%, whereas they have been assumed to be equal in most previous studies. Then, the indirect measurement method is studied from a perspective of theoretical genetics based on the diffusion approximation. A good agreement between two approaches suggests that diffusion approximation can contribute to provide empirical parameters with a cost‐effective method. Abstract : Accommodation coefficients are defined based on the rates at which the molecules change their phase at an interface. Direct calculations based on molecular dynamics simulation and indirect measurements based on a diffusion approximation successfully predict accommodation coefficients to be used in continuum‐level models. The development of new approach can contribute to better accuracy of models to analyze phase transition phenomena.